On sum and stability of g-frames in Hilbert spaces. Issue 8 (3rd August 2018) - Li, Dongwei; Leng, Jinsong; Huang, Tingzhu; Sun, Guomin
Abstract: In this paper, we give some new results on sum and stability of g-frames in Hilbert spaces. Since the finite sum of g-frames may not be a g-frame for the Hilbert space, we give a necessary and sufficient condition and some sufficient conditions for the finite sum of g-frames to be a g-frame. We also show that every g-sequence in Hilbert space can be expanded to a tight g-frame by adding a linear bounded operator. Moreover, we obtain some sufficient conditions under which g-frames (and the finite sum of g-frames) are stable under small perturbations.